Synergistic Integration of Pomegranate Peel Extract and Nanocrystalline Delivery Systems: A Comprehensive Analysis of Phytochemical Efficacy, Antimicrobial Action, And Therapeutic Potential in Modern Oncology and Regenerative Medicine (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The utilization of agro-industrial byproducts, specifically the rind and peel of Punica granatum, has emerged as a cornerstone of green pharmacology and sustainable nanomedicine. This research article provides an exhaustive examination of Pomegranate Peel Extract (PPE) and its bioactive constituents, such as punicalagin, gallic acid, and ellagic acid, in the context of advanced drug delivery and therapeutic intervention. By synthesizing data from phytochemical profiling and nano-technological applications, this study investigates how PPE-mediated synthesis of metallic nanoparticles and the encapsulation of extracts within calcium carbonate ,nanocrystals and electrospun nanofibers significantly enhance bioavailability and targeted action. The article further explores the potent antimicrobial properties of PPE in food preservation and wound healing, its role in inhibiting pancreatic and cervical tumor growth through the targeting of tumor-initiating cells and mitochondrial pathways, and its neurobehavioral impact on model organisms like Danio rerio. Through extensive theoretical elaboration, this paper argues that the transition from crude extract application to nano-encapsulated delivery systems represents a paradigm shift in treating chronic inflammation, acute myocardial infarction, and multi-drug resistant microbial infections.